Child and Adolescent Health and Health Care Quality: Measuring What Matters - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Increasing public investments in health care services for low-income and special needs children and adolescents in the United States have raised questions about whether these efforts improve their health outcomes. Yet it is difficult to assess the general health status and health care quality for younger populations, especially those at risk of poor health outcomes, because the United States has no national information system that can provide timely, comprehensive, and reliable indicators in these areas for children and adolescents. Without such a system in place, it is difficult to know whether and how selected health care initiatives and programs contribute to children's health status. Child and Adolescent Health and Health Care Quality identifies key advances in the development of pediatric health and health care quality measures, examines the capacity of existing federal data sets to support these measures, and considers related research activities focused on the development of new measures to address current gaps. This book posits the need for a comprehensive strategy to make better use of existing data, to integrate different data sources, and to develop new data sources and collection methods for unique populations. Child and Adolescent Health and Health Care Quality looks closely at three areas: the nature, scope, and quality of existing data sources; gaps in measurement areas; and methodological areas that deserve attention. Child and Adolescent Health and Health Care Quality makes recommendations for improving and strengthening the timeliness, quality, public transparency, and accessibility of information on child health and health care quality. This book will be a vital resource for health officials at the local, state, and national levels, as well as private and public health care organizations and researchers.
Keywords: Health and Medicine

Patient-Centered Cancer Treatment Planning: Improving the Quality of Oncology Care: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Each year approximately 1.5 million people are diagnosed with cancer in the United States, most of whom inevitably face difficult decisions concerning their course of care. Recognizing challenges associated with cancer treatment, the National Coalition for Cancer Survivorship (NCCS) and the National Cancer Policy Forum (NCPF) of the Institute of Medicine (IOM) hosted a public workshop in Washington, DC on February 28 and March 1, 2011, entitled Patient-Centered Cancer Treatment Planning: Improving the Quality of Oncology Care. This workshop summary includes an overview of patient-centered care and cancer treatment planning, as well as subject areas on shared decision making, communication in the cancer care setting, and patient experiences with cancer treatment. Best practices, models of treatment planning, and tools to facilitate their use are also discussed, along with policy changes that may promote patient-centeredness by enhancing patient's understanding of and commitment to the goals of treatment through shared decision-making process with their healthcare team from the moment of diagnosis onward. Moreover, Patient-Centered Cancer Treatment Planning emphasizes treatment planning for patients with cancer at the time diagnosis.
Keywords: Health and Medicine

Measuring Food Insecurity and Assessing Sustainability of Global Systems: Report of a Workshop - National Research Council (The National Academies Press, 2011)
There are few areas of human endeavor in which the challenge of sustainability is clearer than in food and agriculture. Farmers and animal keepers must use natural resources--the physical environment of soil, water, and the sun--in ways that generate a continuous supply of food adequate to satisfy people's biological needs for survival and their economic demands. Degradation of soil, inappropriate management of water, and the use of practices that have negative effects on the climate may increase food security in the short run, but will decrease output over time and threaten the survival of future generations. Sustainable management of natural resources and the environment is fundamental to future food security. Action by governments and other agents within and outside the food system may help or hinder sustainability. There is much evidence showing that the current global food system is not sustainable. Measuring Food Insecurity and Assessing the Sustainability of Global Food Systems summarizes a National Research Council workshop, held in February 2011, which explored the availability and quality of commonly used indicators for food security and malnutrition; poverty; and natural resources and agricultural productivity. The workshop was organized around the three broad dimensions of sustainable food security: availability, access, and utilization. Within these topics, the workshop aimed to review the existing data to encourage action and identify the knowledge gaps. A second workshop, held in May 2011, examined ways to sustainably increase global food supplies, natural resource constraints, and necessary policies. A report of that workshop will be available later this year.
Keywords: Health and Medicine

For the Public's Health: The Role of Measurement in Action and Accountability - Institute of Medicine (The National Academies Press, 2011)
Despite having the costliest medical care delivery system in the world, Americans are not particularly healthy. Recent international comparisons show that life expectancy in the U.S. ranks 49th among all nations, and infant mortality rates are higher in the U.S. than in many far less affluent nations. While these statistics are alarming, the bigger problem is that we do not know how to reverse this trend. Our lack of knowledge is due in large part to significant inadequacies in the health system for gathering, analyzing, and communicating health information about the population. To inform the public health community and all other sectors that contribute to population health, For the Public's Health: The Role of Measurement in Action and Accountability reviews current approaches for measuring the health of individuals and communities and creates a roadmap for future development. This book, the first of three in a series, focuses on data and measurement-not as ends in themselves, but rather tools to inform the myriad programs, policies, and processes developed or undertaken by governmental public health agencies and their many partners in the health system. For the Public's Health seeks to reinstate the proper and evidence-based understanding of health as not merely the result of medical or clinical care but the result of the sum of what we do as a society to create the conditions in which people can be healthy. To achieve this goal, the book suggests changes in the processes, tools, and approaches used to gather information about health outcomes and their determinants. The book also recommends developing an integrated and coordinated system in which all parties-including governmental and private sector partners at all levels-have access to timely and meaningful data to help foster individual and community awareness and action.
Keywords: Health and Medicine

Public Health Effectiveness of the FDA 510(k) Clearance Process: Measuring Postmarket Performance and Other Select Topics: Workshop Report - Institute of Medicine (The National Academies Press, 2011)
The Food and Drug Administration (FDA) is responsible for ensuring that medical devices are safe and effective before they go on the market. Section 510(k) of the Federal Food, Drug, and Cosmetic Act requires a manufacturer of medical devices to notify FDA of its intent to market a medical device at least 90 days in advance. That window of time allows FDA to evaluate whether the device is substantially equivalent to a product already legally on the market (called a predicate), in which case the device does not need to go through the premarket approval (PMA) process.
Keywords: Health and Medicine

Clinical Preventive Services for Women: Closing the Gaps - Institute of Medicine (The National Academies Press, 2011)
Women suffer disproportionate rates of chronic disease and disability from some conditions, and often have high out-of-pocket health care costs. The passage of the Patient Protection and Affordable Care Act of 2010 (ACA) provides the United States with an opportunity to reduce existing health disparities by providing an unprecedented level of population health care coverage. The expansion of coverage to millions of uninsured Americans and the new standards for coverage of preventive services that are included in the ACA can potentially improve the health and well-being of individuals across the United States. Women in particular stand to benefit from these additional preventive health services. Clinical Preventive Services for Women reviews the preventive services that are important to women's health and well-being. It recommends that eight preventive health services for women be added to the services that health plans will cover at no cost. The recommendations are based on a review of existing guidelines and an assessment of the evidence on the effectiveness of different preventive services. The services include improved screening for cervical cancer, sexually transmitted infections, and gestational diabetes; a fuller range of contraceptive education, counseling, methods, and services; services for pregnant women; at least one well-woman preventive care visit annually; and screening and counseling for interpersonal and domestic violence, among others. Clinical Preventive Services for Women identifies critical gaps in preventive services for women as well as measures that will further ensure optimal health and well-being. It can serve as a comprehensive guide for federal government agencies, including the Department of Health and Human Services and the Center for Disease Control and Prevention; state and local government agencies; policy makers; health care professionals; caregivers, and researchers.
Keywords: Health and Medicine

Establishing Precompetitive Collaborations to Stimulate Genomics-Driven Product Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Despite the many basic research discoveries in genetics, relatively few gene-based treatments, drugs, or preventative measures have been developed. One way to bridge this gap may be for industry, academia, and government to develop partnerships that share resources while distributing risk. However, intellectual property protections and other barriers can inhibit collaborative efforts. The Institute of Medicine held a workshop on July 22, 2010, to explore these issues and develop solutions.
Keywords: Health and Medicine

Engineering a Learning Healthcare System: A Look at the Future: Workshop Summary - Institute of Medicine; National Academy of Engineering (The National Academies Press, 2011)
Improving our nation's healthcare system is a challenge which, because of its scale and complexity, requires a creative approach and input from many different fields of expertise. Lessons from engineering have the potential to improve both the efficiency and quality of healthcare delivery. The fundamental notion of a high-performing healthcare system--one that increasingly is more effective, more efficient, safer, and higher quality--is rooted in continuous improvement principles that medicine shares with engineering. As part of its Learning Health System series of workshops, the Institute of Medicine's Roundtable on Value and Science-Driven Health Care and the National Academy of Engineering, hosted a workshop on lessons from systems and operations engineering that could be applied to health care.
Keywords: Health and Medicine

Finding What Works in Health Care: Standards for Systematic Reviews - Institute of Medicine (The National Academies Press, 2011)
Healthcare decision makers in search of reliable information that compares health interventions increasingly turn to systematic reviews for the best summary of the evidence. Systematic reviews identify, select, assess, and synthesize the findings of similar but separate studies, and can help clarify what is known and not known about the potential benefits and harms of drugs, devices, and other healthcare services. Systematic reviews can be helpful for clinicians who want to integrate research findings into their daily practices, for patients to make well-informed choices about their own care, for professional medical societies and other organizations that develop clinical practice guidelines.
Keywords: Health and Medicine

Clinical Practice Guidelines We Can Trust - Institute of Medicine (The National Academies Press, 2011)
Advances in medical, biomedical and health services research have reduced the level of uncertainty in clinical practice. Clinical practice guidelines (CPGs) complement this progress by establishing standards of care backed by strong scientific evidence. CPGs are statements that include recommendations intended to optimize patient care. These statements are informed by a systematic review of evidence and an assessment of the benefits and costs of alternative care options. Clinical Practice Guidelines We Can Trust examines the current state of clinical practice guidelines and how they can be improved to enhance healthcare quality and patient outcomes. Clinical practice guidelines now are ubiquitous in our healthcare system. The Guidelines International Network (GIN) database currently lists more than 3,700 guidelines from 39 countries. Developing guidelines presents a number of challenges including lack of transparent methodological practices, difficulty reconciling conflicting guidelines, and conflicts of interest. Clinical Practice Guidelines We Can Trust explores questions surrounding the quality of CPG development processes and the establishment of standards. It proposes eight standards for developing trustworthy clinical practice guidelines emphasizing transparency; management of conflict of interest ; systematic review—guideline development intersection; establishing evidence foundations for and rating strength of guideline recommendations; articulation of recommendations; external review; and updating. Clinical Practice Guidelines We Can Trust shows how clinical practice guidelines can enhance clinician and patient decision-making by translating complex scientific research findings into recommendations for clinical practice that are relevant to the individual patient encounter, instead of implementing a one size fits all approach to patient care. This book contains information directly related to the work of the Agency for Healthcare Research and Quality (AHRQ), as well as various Congressional staff and policymakers. It is a vital resource for medical specialty societies, disease advocacy groups, health professionals, private and international organizations that develop or use clinical practice guidelines, consumers, clinicians, and payers.
Keywords: Health and Medicine

Patients Charting the Course: Citizen Engagement and the Learning Health System: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
As past, current, or future patients, the public should be the health care system's unwavering focus and serve as change agents in its care. Taking this into account, the quality of health care should be judged not only by whether clinical decisions are informed by the best available scientific evidence, but also by whether care is tailored to a patient's individual needs and perspectives. However, too often it is provider preference and convenience, rather than those of the patient, that drive what care is delivered. As part of its Learning Health System series of workshops, the Roundtable on Value & Science-Driven Health Care hosted a workshop to assess the prospects for improving health and lowering costs by advancing patient involvement in the elements of a learning health system.
Keywords: Health and Medicine

Generating Evidence for Genomic Diagnostic Test Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Ten years after the sequencing of the human genome, scientists have developed genetic tests that can predict a person's response to certain drugs, estimate the risk of developing Alzheimer's disease, and make other predictions based on known links between genes and diseases. However, genetic tests have yet to become a routine part of medical care, in part because there is not enough evidence to show they help improve patients' health. The Institute of Medicine (IOM) held a workshop to explore how researchers can gather better evidence more efficiently on the clinical utility of genetic tests. Generating Evidence for Genomic Diagnostic Test Development compares the evidence that is required for decisions regarding clearance, use, and reimbursement, to the evidence that is currently generated. The report also addresses innovative and efficient ways to generate high-quality evidence, as well as barriers to generating this evidence. Generating Evidence for Genomic Diagnostic Test Development contains information that will be of great value to regulators and policymakers, payers, health-care providers, researchers, funders, and evidence-based review groups.
Keywords: Health and Medicine

Informing the Future: Critical Issues in Health, Sixth Edition - Institute of Medicine (The National Academies Press, 2011)
This report illustrates the work of IOM committees in selected, major areas in recent years, followed by a description of IOM's convening and collaborative activities and fellowship programs. The last section provides a comprehensive bibliography of IOM reports published since 2007.
Keywords: Health and Medicine

The Richard and Hinda Rosenthal Lecture 2011: New Frontiers in Patient Safety - Institute of Medicine; Institute of Medicine (The National Academies Press, 2011)
More than 10 years ago, the IOM released its landmark report on patient safety, To Err is Human: Building a Safer Health System. The 2011 Rosenthal Lecture featured the Honorable Kathleen G. Sebelius, Secretary of the U.S. Department of Health and Human Services, who presented the new steps that HHS is taking to improve patient safety. A panel of leaders in patient safety followed to discuss patient safety progress and opportunities.
Keywords: Health and Medicine

Allied Health Workforce and Services: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
The demand for health care is growing as the nation ages and seeks to provide coverage for the millions of Americans who lack health insurance. At the same time, escalating costs have led to a variety of initiatives to make the delivery of health care more effective and efficient. The allied health workforce is critical to the success of these efforts. The IOM held a workshop May 9-10, 2011, to examine the current allied health care workforce and consider how it can contribute to improving health care access, quality, and effectiveness.
Keywords: Health and Medicine

Digital Infrastructure for the Learning Health System: The Foundation for Continuous Improvement in Health and Health Care: Workshop Series Summary - Institute of Medicine (The National Academies Press, 2011)
Like many other industries, health care is increasingly turning to digital information and the use of electronic resources. The Institute of Medicine's Roundtable on Value & Science-Driven Health Care hosted three workshops to explore current efforts and opportunities to accelerate progress in improving health and health care with information technology systems.
Keywords: Health and Medicine

Innovations in Health Literacy Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Nearly nine out of 10 adults have difficulty using everyday health information to make good health decisions. The Institute of Medicine (IOM) Roundtable on Health Literacy held a meeting on May 27, 2010, to explore areas for research in health literacy, the relationship between health literacy and health disparities, and ways to apply information technology to improve health literacy.
Keywords: Health and Medicine

State and Local Policy Initiatives to Reduce Health Disparities: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Although efforts to reduce health disparities receive attention at the national level, information on the successes of state and local efforts are often not heard. On May 11, 2009, the Institute of Medicine held a public workshop to discuss the role of state and local policy initiatives to reduce health disparities. The workshop brought together stakeholders to learn more about what works in reducing health disparities and ways to focus on localized efforts when working to reduce health disparities.
Keywords: Health and Medicine

Learning What Works: Infrastructure Required for Comparative Effectiveness Research: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
It is essential for patients and clinicians to have the resources needed to make informed, collaborative care decisions. Despite this need, only a small fraction of health-related expenditures in the United States have been devoted to comparative effectiveness research (CER). To improve the effectiveness and value of the care delivered, the nation needs to build its capacity for ongoing study and monitoring of the relative effectiveness of clinical interventions and care processes through expanded trials and studies, systematic reviews, innovative research strategies, and clinical registries, as well as improving its ability to apply what is learned from such study through the translation and provision of information and decision support.
Keywords: Health and Medicine

Toward Precision Medicine: Building a Knowledge Network for Biomedical Research and a New Taxonomy of Disease - National Research Council (The National Academies Press, 2011)
Motivated by the explosion of molecular data on humans-particularly data associated with individual patients-and the sense that there are large, as-yet-untapped opportunities to use this data to improve health outcomes, Toward Precision Medicine explores the feasibility and need for "a new taxonomy of human disease based on molecular biology" and develops a potential framework for creating one. The book says that a new data network that integrates emerging research on the molecular makeup of diseases with clinical data on individual patients could drive the development of a more accurate classification of diseases and ultimately enhance diagnosis and treatment. The "new taxonomy" that emerges would define diseases by their underlying molecular causes and other factors in addition to their traditional physical signs and symptoms. The book adds that the new data network could also improve biomedical research by enabling scientists to access patients' information during treatment while still protecting their rights. This would allow the marriage of molecular research and clinical data at the point of care, as opposed to research information continuing to reside primarily in academia. Toward Precision Medicine notes that moving toward individualized medicine requires that researchers and health care providers have access to very large sets of health- and disease-related data linked to individual patients. These data are also critical for developing the information commons, the knowledge network of disease, and ultimately the new taxonomy.
Keywords: Health and Medicine